Charged kaon femtoscopic correlations in pp collisions at √s=7 TeV - Abelev, B.; Adam, J.; Adamova, D.; Adare, A. M.; Aggarwal, M. M.; Rinella, G. Aglieri; Agnello, M.; Agocs, A. G.; Agostinelli, A.; Ahammed, Z.; Ahmad, N.; Masoodi, A. Ahmad; et al. (AMER PHYSICAL SOC, 2013)
Correlations of two charged identical kaons (KchKch) are measured in pp collisions at root s = 7 TeV by the ALICE experiment at the Large Hadron Collider (LHC). One-dimensional (KKch)-K-ch correlation functions are constructed in three multiplicity and four transverse momentum ranges. The (KKch)-K-ch femtoscopic source parameters R and lambda are extracted. The (KKch)-K-ch correlations show a slight increase of femtoscopic radii with increasing multiplicity and a slight decrease of radii with increasing transverse momentum. These trends are similar to the ones observed for pi pi and K-s(0) K-s(0) correlations in pp and heavy-ion collisions. However at high multiplicities, there is an indication that the one-dimensional correlation radii for charged kaons are larger than those for pions in contrast to what was observed in heavy-ion collisions at the Relativistic Heavy-Ion Collider. DOI:10.1103/PhysRevD.87.052016
Keywords: BOSE-EINSTEIN CORRELATIONS; COULOMB CORRECTIONS; INTERFEROMETRY; INTERFERENCE; DECAYS; Astronomy & Astrophysics; Physics